NEW IN THE METHODS OF RESEARCHES FROM THE EXPOSURE OF PERSPECTIVE AMBER DEPOSITS - KRYNYTSKA, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
On the example of local area researched conditions of bedding of amber deposits. The method of study of territories, perspective on an exposure industrial amber deposits is complemented.